ANALISIS DETERMINAN KEPATUHAN PEGAWAI TERHADAP KAWASAN TANPA ROKOK DI DINAS PENDIDIKAN PROVINSI SULAWESI SELATAN - Mega Marindrawati Rochka; Suci Rahmadani; Andi Awaliya Anwar (Dian Nuswantoro Semarang, 2019)
The policy to implement a Smoking Area (KTR) has been agreed as the main intervention strategy to control non-communicable diseases. Regulations in the form of Non-Smoking Regional Law (KTR) have also been approved in various countries as an embodiment of tobacco regulation in the world. Implementation of issued regional policies must be carried out by all Local Governments in Indonesia. This study discusses the determinants associated with employees in the Non-Smoking Area in the Education Office of South Sulawesi Province. This research is a type of quantitative research using Cross-Sectional Studies. The population in this study was 183 people. Sampling was done using the Total Sampling method so that a total sample of 183 people were obtained. Data processing and analysis using the SPSS program. Data analysis is based on the Chi-Square Test statistical test. The results showed there was a relationship between smoking relationships (p = 0,000), there was a relationship between attitudes (p 0,000), there was a relationship between social support (p = 0,000) and employee associations regarding smoking area regulations in the South Sulawesi Provincial Education Office and none the relationship between knowledge (p = 0.288) and employee associations regarding regional regulations in the South Sulawesi Provincial Education Office.